Quantum yield and photosynthetic parameters of marine microalgae from the southern Arctic Ocean, Svalbard - Andrew McMinn; Hegseth, EN (2004)
The quantum yield and photosynthetic parameters of phytoplankton and sea ice microalgal communities were assessed from the Arctic Ocean and fjords of northern Svalbard. The phytoplankton community in Fram Strait was dominated by Phaeocystis while on Norskebanken it was dominated by diatoms. The quantum yield showed maximum values of 0.64 at 20-40 m below the surface and were consistent with nutrient replete waters elsewhere. Sea ice infiltration communities were widespread and dominated by Phaeocystis. This is the first record of an Arctic infiltration ice community. Quantum yields were relatively low (0.247). Bottom ice communities, which were dominated by Nitzschia frigida, were extremely restricted and had moderate quantum yields (0.427). Communities growing on multiyear ice had quantum yields of only 0.126. All ice communities were well adapted to their light environment.